2022
DOI: 10.1002/ar.25055
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the role and mechanism of gut microbiota in methamphetamine addiction using antibiotic treatment followed by fecal microbiota transplantation

Abstract: Recently, the role of the gut microbiota in the context of drug addiction has attracted the attention of researchers; however, the specific effects and underlying mechanisms require further exploration. To accomplish this, C57BL/6 mice were firstly treated with methamphetamine (MA). Conditioned place preference (CPP) behavior changes, gut permeability and function, microglial activation, and inflammatory cytokine expression were systematically analyzed in antibiotics-treated mice with microbiota depletion and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 50 publications
(74 reference statements)
1
2
0
Order By: Relevance
“…30,31 For example, the formation of MA addiction was inhibited through the depletion of gut microbiota with antibiotics, while the inhibition was reversed by microbiota transplantation. 32 A similar conclusion was confirmed by Chen et al in morphine addiction models, where the formation and treatment effect of addiction was through microbiota. 33 In addition, an improvement in impulsivity induced by probiotics was also identified in a double-blind randomized clinical study.…”
supporting
confidence: 62%
See 1 more Smart Citation
“…30,31 For example, the formation of MA addiction was inhibited through the depletion of gut microbiota with antibiotics, while the inhibition was reversed by microbiota transplantation. 32 A similar conclusion was confirmed by Chen et al in morphine addiction models, where the formation and treatment effect of addiction was through microbiota. 33 In addition, an improvement in impulsivity induced by probiotics was also identified in a double-blind randomized clinical study.…”
supporting
confidence: 62%
“…Moreover, microbiota disruption has been proposed as a causal effect of these alterations 30,31 . For example, the formation of MA addiction was inhibited through the depletion of gut microbiota with antibiotics, while the inhibition was reversed by microbiota transplantation 32 . A similar conclusion was confirmed by Chen et al.…”
Section: Introductionmentioning
confidence: 58%
“…Chen et al discovered that the relative abundances of pathogenic bacteria improved while those of probiotics were reduced by MA exposure, with corresponding metabolomics alterations [37]. Wang et al revealed that MA-induced mice treated with antibiotics exhibit weaker conditioned place preference (CPP), but CPP formation was erased by fecal microbiota transplantation [38]. The above studies suggest that the psychological and behavioral changes induced by MA may be related to gut microbiota.…”
Section: Introductionmentioning
confidence: 99%
“…One particularly intriguing aspect is the microbial impact over psychoneurological functions of the host, which has led to the concept of the “gut‐brain axis” (Sharon et al, 2016). The article by Wang et al explores the mechanistic connections between the gut microbiota and metamphetamine addiction in mice (Wang et al, 2022) and sheds light on their reciprocal influence. Their findings show that intraperitoneal metamphetamine injection induces changes in the composition of the gut microbiota and the intestinal epithelial barrier and that in turn, manipulation of the gut microbiota by administration of antibiotics or fecal transplant modifies the behavioral response to metamphetamine administration.…”
Section: Introductionmentioning
confidence: 99%